Preparation and Characterization of Natural Zeolite Minerals to Reduce Free Fatty Acid Levels in Used Cooking Oil - Fadliah Fadliah; Riskaviana Kurniawati; Reno Pratiwi; Aqlyna Fattahanisa; Wiwik Dahani; Syamidi Patian; Emmy Fatmi Budhya (Penerbitan Universitas Trisakti, 2022)
Zeolite as a catalyst can increase its activity by carrying out physical and chemical activation processes. Physical activation can be activated by reducing the size of the zeolite through grinding and sieving methods, from the physical activation process it can increase the surface area of the zeolite. In this study, zeolite was chemically activated by acid activation method by immersing natural zeolite with HCl and HF. The oxide compound in the activated zeolite was characterized using XRF. The activated zeolite was used to reduce the free fatty acid levels with variations in the addition of 7 to 10 grams of zeolite. The content of free fatty acids is then compared with the quality requirements of cooking oil according to SNI 01-3741-2013. The results of the research conducted showed that there were differences in the content of oxide compounds in zeolite before and before activation with differences in SiO2 content, namely 69.4% before activation and an increase of 82.1% after activation. The results of the state test including physical properties, odor, and taste tests of used cooking oil that have been purified indicate that used cooking oil that has been purified meets the quality requirements of cooking oil based on SNI 01-3741-2013. Used cooking oil that has been purified has a normal taste, does not smell. rancid and yellow. The content of free fatty acids meets the requirements of SNI 01-3741-2013 for all variations of the addition of zeolite with the highest decreasing value obtained at the addition of 10 g of zeolite with a free fatty acid content value of 0.22%.